Thank you to our reviewers. (7th December 2015) - Unknown
Abstract : The Editor, Publishers, and Board of Language Teaching would like to thank the following readers who have generously assisted with their time and expertise reviewing manuscripts in the preparation of volume 48. Reviewers are absolutely critical to the functioning of any peer reviewed journal, and we are very much in their debt.